Sie sind auf Seite 1von 18

# I.

FUNCTIONS
LESSON 1 : FUNCTIONS and RELATIONS
Relation
A relation is a rule that relates values from a set of values (called the
domain) to a second set of values (called the range).

Function
A function is a relation where each element in the domain is related to only
one value in the range by some rule.

Examples :
Example 1. Which of the following relations are functions?

## f = {(1, 2), (2, 3), (3, 5), (4, 7)}

g= {(1, 3), (1, 4), (2, 5), (2, 6), (3, 7)}
h= {(1, 3), (2, 6), (3, 9), •••, (n, 3n), •••}

Solution.
The relations f and h are functions because no two ordered pairs have the
same x-value but different y-values. Meanwhile, g is not a function because
(1, 3) and (1, 4) are ordered pairs with the same x-value but different y-
values.

## Relations and functions can be represented by mapping diagrams where the

elements of the domain are mapped to the elements of the range using
arrows. In this case, the relation or function is represented by the set of all
the connections represented by the arrows.
Example 2. Which of the following diagram represents relation? function? Example 3. Identify which is a function and which is a relation.

a.) b.)
f g

h
Solution.
Diagram a is a function because it pass the vertical line test while
diagram b is not a function.

EXERCISES:
Identify whether the given diagrams and set of values are function or
relation. Write F if function and R if relation.
1. {(-2, 2), (-1, 1), (0, 0), (1, 1), (2, 2)}
Solution: 2. {(4, 2), (5, 1), (6, 0), (7, -1), (8, -2)}
The relations f and g are functions because each value y in Y is unique for 3. {(1, 2), (5, 3), (-3, 7), (-2, 9), (2, 3)}
a specific value of x. The relation h is not a function because there is at least 4. {(0, 0), (1, 1), (1, -1), (2, 2), (2, -2)}
one element in X for which there is more than one corresponding y-value. 5. 6.
For example, x=3 corresponds to y = b or c. A relation between two sets of
numbers can be illustrated by a graph in the Cartesian plane, and that a
function passes the vertical line test.

## The Vertical Line Test

A graph represents a function if and only if each vertical line
intersects the graph at most once.
7. 8. Examples:
Example 1.

9. 10.

So what this means is for every x less than or equal to –2, we need to graph
the line 2x+8, as if it were the only function on the graph. For every x value
greater than –2, we need to graph x2, as if it were the only function on the
graph. Then we have to “get rid of” the parts that we don’t need. Remember
that we still use the origin as the reference point for both graphs!
LESSON 2: PIECE-WISE FUNCTION See how the vertical line x = −2 acts as a “boundary” line between the two
graphs?
Piece-wise Function Note that the point (–2, 4) has a closed circle on it. Technically, it should
only belong to the 2x+8 function, since that function has the less than or
A piece-wise function is a function which consists of two or more functions equal sign, but since the point is also on the x2 graph, we can just use a
in a specified domain. closed circle as if it appears on both functions.

Some situations can only be described by more than one formula, depending Example 2.
on the value of the independent variable. Evaluate f(x) when x = -3, x = 2, and x = 4. Then graph f(x).
𝒙 + 𝟏, 𝒊𝒇 𝒙 < 𝟐
𝒇(𝒙) = {
−𝟐𝒙 + 𝟕, 𝒊𝒇 𝒙 ≥ 𝟐
Evaluating a piecewise function adds an extra step to the whole proceedings. Example 3.
We have to decide which piece of the function to plug-and-chug into. Since Graph the function defined as shown.
-3 is less than 2, we use the first function to evaluate x = -3.
𝟏 𝟐
f (x) = x + 1 𝒙 𝒇𝒐𝒓 𝒙 < −𝟐
f (-3) = -3 + 1 = -2 𝟐
𝒚 = 𝟎 𝒇𝒐𝒓 − 𝟐 ≤ 𝒙 < 𝟐
The number 2 is our boundary between life, death, and the two pieces of 𝟏 𝟐
our function. Tie-breakers go to the second function, though. { 𝟐 𝒙 𝒇𝒐𝒓 𝒙 ≥ 𝟐
f (x) = -2x + 7
f (2) = -2(2) + 7 = 3
Note that we use small white circles in the graph to indicate that the
The second function continues to be used, from 2 onward to infinity—and
beyond, according to some space-faring toys. endpoint of a curve is not included in the graph, and solid dots to indicate
f (x) = -2x + 7 endpoints that are included.
f (4) = -2(4) + 7 = -1

## To the left of x = 2, f(x) = x + 1.

The graph will go right up to, but not touch, f (2) = 2 + 1 = 3. Then f(x) = -
2x + 7 to the right of and including x = 2. We can also use the points we
evaluated as guides.
Exercises: Example 2.
Find the value of h (b) = 3b2 - 2b + 1 when b = -3.
1. Your favorite dog groomer charges according to your dog’s weight. If
your dog is 15 pounds and under, the groomer charges \$35. If your dog is Solution: Substitute -3 into the function in place of b.
between 15 and 40 pounds, she charges \$40. If your dog is over 40 pounds, h (-3) = 3(-3)2 - 2(-3) + 1
she charges \$40, plus an additional \$2 for each pound. Write a piecewise h (-3) = 3(9) + 6 +1
function that describes what your dog groomer charges. h (b) = 34

## Make a graph using the given piece-wise functions: Example 3.

Given f (x) = x2 - x - 4. If f (k) = 8, what is the value of k?
−𝟐𝒙 + 𝟖 𝒊𝒇 𝒙 ≤ 𝟒
2. 𝒇(𝒙) = { 𝟏
𝒙−𝟐 𝒊𝒇 𝒙 > 𝟒 Solution: Set the function rule equal to 8 and solve for k.
𝟐
x2 - x - 4 = 8
x2 - x - 12 = 0
𝟔 (x - 4)(x + 3) = 0
𝒙−𝟐 𝒊𝒇 𝒙 < 𝟓 x - 4 = 0; x + 3 = 0
𝟓
3. 𝒇(𝒙) = { 𝟐 x = 4; x = -3
𝒙+𝟐 𝒊𝒇 𝒙 ≥ 𝟓
𝟓

Exercises:
LESSON 3: EVALUATING FUNCTIONS Evaluate the following function.
1. f (x) = 2x+4 for x=5
Evaluating a function means replacing the variable in the function, in this 2. f (x) = 4x + 1, find f(2)
case x, with a value from the function’s domain and computing for the 3. f(x) = 3x – 4, find f(5)
result. To denote that we are evaluating f at a for some a in the domain of f, 4. f(x) = 3x2 + 2x + 1, find f(b)
we write f (a). 5. f(x) = 4x + 1, find f(h + 1)
6. Does this two equations represent the same function?
Examples: y = 2x – 7 and f(x) = 7 – 2x

## Example 1. Given g(x) = 4x + 7, find g(−10).

Given the function f (x) = 3x - 5, find f (4). 7. −40 + 7
Solution: Substitute 4 into the function in place of x. f (4) = 3(4) - 5 = 7. 8. 4x + 17
Given the function of 𝒇(𝒙) = √𝟐𝟓 − 𝐱 𝟐 , evaluate the following:
This answer can be thought of as the ordered pair (4, 7). The answer may 9. f (–3)
also be referred to as the image of 4 under f (x). 10. f(-1)
LESSON 4 : OPERATION ON FUNCTIONS Use the functions below to perform the following operations:
f(x) = 2x g(x) = x - 2
h(x) = 𝒙 k(x) = x/2
Their sum is denoted as (f+g)(x) = f(x) + g(x).
Example: f(x) = 2x+3 and g(x) = 𝒙𝟐
6. k(x) ● f(x)
(f+g)(x) = (2x+3) + (𝒙𝟐 ) 7. g(x) - h(x)
(f+g)(x) = 𝒙𝟐 +2x+3 8. h(x) + k(x)
9. f(x) ÷ k(x)
Subtraction : 10. g(x) ● h(x)
Their difference is denoted as (f-g)(x) = f(x) − g(x).
Example: f(x) = 2x+3 and g(x) = 𝒙𝟐
(f-g)(x) = (2x+3) − (𝒙𝟐 )
LESSON 5: COMPOSITE FUNCTION
(f-g)(x) = -x2 +2x + 3
Composite Function
A composite function is a function that depends on another function. It is
Multiplication :
created when one function is subtitled into another function.
Their product is denoted as (f·g)(x) = f(x) · g(x).
Let f and g be functions. The composite functions is denoted by (𝒇 ○ 𝒈), is
Example: f(x) = 2x+3 and g(x) = 𝒙𝟐
defined by (𝒇 ○ 𝒈) = 𝒇[𝒈(𝒙)].
(f·g)(x) = (2x+3)(𝒙𝟐 )
 The process of obtaining a composite function is called function
(f·g)(x) = 2𝒙𝟑 + 3𝒙𝟐 composition, it is a function made another 𝒇(𝒙).

Division : Examples:
Their quotient is denoted as (f/g)(x) = f(x) / g(x).
Example: f(x) = 2x+3 and g(x) = 𝒙𝟐 Given f(x) = x2 + 6 and g(x) = 2x – 1, find:
f(x) = 2x + 3 / x2 1. (f ○ g)(x) = f(2x – 1)
= (2x – 1)2 + 6
Exercises: = 4x2 – 4x + 1 + 6
Given f (x) = 3x + 2, h(x) = 2x+1 and g(x) = 4 – 5x, find the following: = 4x2 – 4x + 7
1. (h + g) (x)
2. (f – h) (x) 2. (g ○ f)(x) = g(x2 + 6)
3. (f × g) (x) = 2(x2 + 6) – 1
4. (f / g) (x) = 2x2 + 12 –1
5. (f ×h) (x) = 2x2 + 11
3. Find the composite function defined by (g ○ f)(x) if f(x) = √(x + 2) and
g(x) = ( 1 – x2 ).
II. RATIONAL EXPRESSIONS
(g ○ f)(x) = g[f(x)] LESSON 6: RATIONAL EQUATIONS
= 1 - x2
= 1 - √(x + 2)2 Rational Expression
= 1 - (x + 2) A rational expression is an expression that can be written as a ratio of two
= (- x - 1) polynomials.
𝟐 𝒙𝟐 +𝟐𝒙+𝟑 𝟓
Exercises: Example: , ,
𝒙 𝒙+𝟏 𝒙−𝟑
Given f(x) = x – 4x + 2
2
g(x) = 3x – 7
k(x) = –6x + 5 h(x) = –9x – 11 Rational Equations
m(x) = x + 1 e(x) = 5x2 – 3  An equation involving rational expressions.
 A rational equation or inequality can be solved for all of x values that
Find the following: satisfy the equation or inequality.
 To solve a rational equation:
1. (f ○ g)(x) (a) Eliminate denominators by multiplying each term of the equation by
2. (k ○ h)(x) the least common denominator.
3. (e ○ m)(x) (b) Note that eliminating denominators may introduce extraneous
4. (f ○ m)(x) solutions. Check the solutions of the transformed equations with the
5. (g ○ e)(x) original equation.
For numbers 6 to 10, use the following functions:
Examples:
𝟐 𝟑 𝟏
f(x) = 2x + 1 g(x) = √𝒙 + 𝟏 Example 1: Solve for x: − =
𝒙 𝟐𝒙 𝟓
𝟐𝒙+𝟏 𝟐 𝟑 𝟏
q(x) = x2 - 2x + 2 F(x) = [x] + 1 p(x) =
𝒙−𝟏
𝟏𝟎𝒙 ( ) − 𝟏𝟎𝒙 ( ) = 𝟏𝟎𝒙 ( )
𝒙 𝟐𝒙 𝟓
20 – 15 = 2x
6. (g ○ f)(x) 5 = 2x
7. (q ○ f)(x) 𝟓
=x
8. (f ○ p)(x) 𝟐
9. ( F ○ p)(5)
10. (f ○ g)(x) Example 2: In an inter – barangay basketball league, the team from
Barangay Culiat has won 12 out of 25 games, a winning percentage of 48%.
How many games should they win in a row to improve their win percentage
to 60%?
𝟏𝟐 + 𝒙
= 𝟎. 𝟔
𝟐𝟓+𝒙
LESSON 7 : RATIONAL INEQUALITIES
12 + x = (25 + x)(0.6) Procedure for Solving Rational Inequalities:
12 + x = 0.6(25) + 0.6(x) (a) Rewrite the inequality as a single rational expression on one side of the
x – 0.6x = 15 – 12 inequality symbol and 0 on the other side.
0.4x = 3 (b) Determine over what intervals the rational expression takes on positive
x = 7.5 or 8 and negative values.
i. Locate the x values for which the rational expression is zero or undefined
𝒙 𝟏 𝟖 (factoring the numerator and denominator is a useful strategy).
Example 3: Solve for x: − =
𝒙+𝟐 𝒙−𝟐 𝒙𝟐 −𝟒 ii. Mark the numbers found in (i) on a number line. Use a shaded circle to
𝒙 𝟏 𝟖
indicate that the value is included in the solution set, and a hollow circle to
− = indicate that the value is excluded. These numbers partition the number
𝒙+𝟐 𝒙−𝟐 (𝒙+𝟐)(𝒙−𝟐)
𝒙 𝟏 𝟖 line into intervals.
[(𝒙 + 𝟐)(𝒙 − 𝟐)] ( ) − ((𝒙−𝟐)) = [(𝒙 + 𝟐)(𝒙 − 𝟐)] ((𝒙+𝟐)(𝒙−𝟐))
𝒙+𝟐 iii. Select a test point within the interior of each interval in (ii). The sign of
𝒙(𝒙 − 𝟐) − (𝒙 + 𝟐) = 𝟖 the rational expression at this test point is also the sign of the rational
𝒙𝟐 − 𝟑𝒙 − 𝟏𝟎 = 𝟎 expression at each interior point in the aforementioned interval.
𝒙𝟐 − 𝟑𝒙 − 𝟏𝟎 = 𝟎 → (𝒙 + 𝟐)(𝒙 − 𝟓) = 𝟎 iv. Summarize the intervals containing the solutions.
x+2=0 or x–5=0 INTERVAL SET NOTATION GRAPH
x = -2 or x=5 (a, b) {x | a < x <b} ○ ○
Since x = - 2 makes the original equation undefined, x = 5 is the only a b
solution. [a, b) {x | a ≤ x ≤ b} ● ●
a b
Exercises: [a, b) {x | a ≤ x < b} ● ○
a b
Solve for x:
𝟓 𝟏 𝟏 (a, b] {x | a < x ≤ b} ○ ●
1. − = a b
𝒙 𝟑 𝒙
(a, ∞) {x | a < x} ○
𝟏 𝟑 a
2. − 𝟏 =
𝒙 𝟒𝒙 [a, ∞) {x | a ≤ x} ●
a
𝒙 𝟖
3. = (-∞, b) {x | x < b} ○
𝒙+𝟑 𝒙+𝟔
b
𝟓 𝟏 𝟐 (-∞, b] {x | x ≤ b} ●
4. = − b
𝟔𝒙𝟐 −𝟗𝒙 𝟐𝒙−𝟑 𝟑𝒙
(-∞,∞) {set of all real
𝟐𝟒 𝒙−𝟏 𝒙+𝟑 numbers}
5. − =
𝒙𝟐 −𝒙−𝟔 𝒙+𝟐 𝟑−𝒙
Examples: 𝟏(𝟑𝒙 − 𝟏) − 𝟏(𝒙 + 𝟐)
<𝟎
Example 1. 𝒙+𝟐
𝟐𝒙 𝟑𝒙 − 𝟏 − 𝒙 − 𝟐
≥1 <𝟎
𝒙+𝟏
𝒙+𝟐
(a) Rewrite the inequality as a single rational expression. 𝟐𝐱 − 𝟑
𝟐𝒙
–1≥0 <𝟎
𝒙+𝟏 𝒙+𝟐
𝟐𝒙−𝒙−𝟏 2x-3 = 0 x+2 = 0
≥0 𝟐𝒙 𝟑
𝒙+𝟏
𝒙−𝟏 = x = -2
≥0 𝟐 𝟐
𝒙+𝟏
(b) The rational expression will be zero for x = 1 and undefined for x = –1. ○ ○
The value x = 1 is included while x = –1 is not. Mark these on the number 𝟑
line. Use a shaded circle for x = 1 (a solution) and an unshaded circle for x -2
𝟐
INTERVAL x < -2 𝟑 𝟑
= -1 (not a solution). -2 < x < x>
𝟐 𝟐
○ ● TEST POINT -3 0 2
-1 1
2x – 3 - - +
(c) Choose convenient test points in the intervals determined by –1 and 1 to
x+2 - + +
determine the sign of in these intervals. Construct a table of signs as shown 𝟐𝒙 − 𝟑 + - +
below.
𝒙+𝟐
interval notation: set notation:
INTERVAL x < -1 -1 < x ≤ 1 x≥1 𝟑 𝟑
TEST POINT x = -2 x=0 x=2 (-2, ) {x | -2 < x < }
𝟐 𝟐
𝒙−𝟐
x-1 - - + Example 3. >𝟎
𝒙+𝟑
x+1 - + + x–2=0 x+3=0
𝒙−𝟏 + - + x=2 x = -3
𝒙+𝟏 ○ ○
-3 2
(d) Since we are looking for the intervals where the rational expression is INTERVAL x < -3 -3 < x < 2 x>2
positive or zero, we determine the solution to be the set {x | x < -1}∪{x|x ≥1}. TEST POINT -4 0 3
Plot this set on the number line. x–2 - - +
○ ● x+3 - + +
-1 1 𝒙−𝟐 + - +
Example 2.
𝟑𝒙 − 𝟏 𝒙+𝟑
−𝟏<𝟎 interval notation: set notation:
𝒙+𝟐 (-∞, -3) ∪ (2, ∞) {x | x < -3} ∪ {x | x > 2}
Exercises:
Write the interval notation and set notation of the following graphs.
1. ● Example 2:
𝒙𝟑 − 𝟐𝒙
0 𝒈 (𝒙) = 𝟐
𝟐𝒙 −𝟏𝟎
2. ○ ●
𝟎 = 𝒙𝟑 − 𝟐𝒙
-1 5
= 𝒙(𝒙𝟐 − 𝟐)
3. ○
𝒙𝟐 − 𝟐 = 𝟎
-2
4. ● ● 𝒙𝟐 = 𝟐
-2 2 𝒙 = ±√𝟐
5. ●
6 Thus there are three roots, or
LESSON 8: RATIONAL FUNCTION x-intercepts: 0, +√𝟐, -√𝟐
𝒑(𝒙)
A rational function is a function of the form 𝒇(𝒙) = where 𝒑(𝒙) and
𝒒(𝒙)
𝒒(𝒙) are polynomial functions and 𝒒(𝒙) is not zero polynomial (i. e., 𝒒(𝒙) Example 3:
≠ 0). The domain of 𝒇(𝒙) is all values of x where 𝒒(𝒙) ≠ 0. 𝒙𝟐 − 𝟑𝒙
𝒇(𝒙) =
𝟐𝒙−𝟐
The bottom polynomial is 2x-2,
Horizontal Asymptote (HA)
 If the degree of the numerator is greater than the degree of denominator which factors into: 𝟐(𝒙 − 𝟏).
then HA = no asymptote.
 If the degree of the numerator is equal to the degree of denominator then And the factor (x-1) means there
HA is the ratio of their coefficient. is a vertical asymptote at x=1
 if the degree of numerator is less than the degree of denominator, the (because 1-1=0).
HA = 0.
Examples: Exercises:
(𝒙𝟐 −𝟑𝒙−𝟐) Graph the following rational functions.
Example 1: 𝒇(𝒙) = 1. 𝒈(𝒙) = 𝟐
𝒙−𝟏
(𝒙𝟐 −𝟒)
(𝒙 −𝟗)
The domain of this function includes 𝒙+𝟏
all values of x, except where x2 – 4 = 0. 2. 𝒇(𝒙) =
𝒙−𝟓
x2 – 4 = (x + 2)(x – 2) 𝒙𝟐 − 𝟒
3. 𝒇(𝒙) =
x+2=0 x – 2 =0 𝒙−𝟐

x = -2 x=2
Therefore, the domain includes all
x is not equal to 2 or −2.
𝟐𝒙+𝟏
III. INVERSE OF A FUNCTION Example 3. Find the inverse of a rational function f(x) =
𝟐𝒙+𝟏
𝟑𝒙−𝟒
.
LESSON 9 : FINDING THE INVERSE OF A FUNCTION y=
𝟑𝒙−𝟒
Definition: Let f be a function with domain A and range B. Then the 𝟐𝒚+𝟏
x=
𝟑𝒚−𝟒
inverse of f, denoted by f-1, is a function with domain B and range A
defined by f-1(y) = x if and only if f(x) = y for any y in B. x (3y – 4) = 2y + 1
3xy – 4x = 2y + 1
To find the inverse of a function: 3xy – 2y = 4x + 1
(a) Write the function in the form y = f(x); y (3x – 2) = 4x + 1
𝟒𝒙 + 𝟏
(b) Interchange the x and y variables; y=
𝟑𝒙−𝟐
(c) Solve for y in terms of x. -1 𝟒𝒙 + 𝟏
f (x) =
𝟑𝒙−𝟐
Property of an inverse of a function
Given a function f(x) and its inverse f-1(x), then the following are true:
● The inverse of f-1(x) = x is f(x).
Exercises:
● f(f-1(x) = x for all x in the domain of f-1. Find the inverse of the following functions.
● f-1(f(x)) = x for all x in the domain of f. 1. f (x) = 2x + 7
𝒙−𝟐
2. f (x) =
𝟑𝒙+𝟓
3. f(x) = -x3 + 2
Examples:
4. f(x) = 5 – 9x
Example 1. Find the inverse of f(x) =3x + 1. 𝟏
y = 3x + 1 5. f(x) = 𝒛 + 𝟕
𝟐
𝟓
x = 3y + 1 6. f(x) = √𝟐𝒙 + 𝟏𝟏
x-1 = 3y 𝟒𝒙
𝒙−𝟏
7. f(x) =
𝟓−𝒙
=𝒚 𝟏+𝟐𝒙
𝟑 8. y=
𝒙−𝟏 𝟕+𝒙
y=
𝟑 9. f(x) = (𝒙 − 𝟐)𝟑 + 𝟏
𝒙−𝟏
(f-1(x) = 10. P(x) = 12x−7
𝟑
Example 2. Find the inverse of g(x) = x3-2.
y = x3-2
x = y3-2
x – 2 = y3
y3 = x – 2
𝟑 𝟑
√𝒚𝟑 = √𝒙 − 𝟐
𝟑
y = √𝒙 − 𝟐
𝟑
g-1(x) = √𝒙 − 𝟐
𝟏
III. EXPONENTIAL EXPRESSIONS Example 2. 𝟒𝟓−𝟗𝒙 =
𝟖𝒙−𝟐
checking:
𝟒
𝟏 𝟏
LESSON 10: EXPONENTIAL EQUATION (𝟐𝟐 ) 5-9x =
(𝟐𝟑 )𝒙−𝟐
𝟒𝟓−𝟗(𝟏𝟓) = 𝟒
()−𝟐
Exponential expression is a mathematical expression consisting of a 𝟖 𝟏𝟓
𝟑𝟔 𝟏
x–c (𝟐𝟐 ) 5-9x = 𝟐−𝟑(𝒙−𝟐) 𝟒𝟓−𝟏𝟓 = 𝟒−𝟑𝟎
constant raised power. It is an expression in the form a∙b + d, where b > 𝟖 𝟏𝟓
𝟕𝟓−𝟑𝟔 𝟏
0, b ≠ 1. 2(5 – 9x) = -3(x-2) 𝟒 𝟏𝟓 = 𝟒−𝟑𝟎
𝟖 𝟏𝟓
𝟏𝟑 𝟐𝟔
Exponential equations are equations in which variables occur as 10 – 18x = -3x + 6 (𝟐𝟐 ) 𝟓 = (𝟐 ) 𝟑 𝟏𝟓
exponents. 𝟏𝟑 𝟕𝟖

For example, exponential equations are in the form 𝒂𝒙 = 𝒃𝒚 . 10 – 6 = 18x - 3x (𝟐𝟐 ) 𝟓 = 𝟐𝟏𝟓
𝟐𝟔 𝟐𝟔
4 = 15x 𝟐𝟓 = 𝟐𝟓
LAWS OF EXPONENTS 𝟒
x=
0
1. x = 1 50 = 1 ; 10000 = 1 𝟏𝟓
𝟏 𝟏 𝟏
2. x-1 = 2-1 = ; 10 -1 =
𝒙 𝟐 𝟏𝟎 Example 3. 𝟑𝒙 = (𝟑𝟐 )𝒙+𝟓 checking:
3. ar. as = ar + s 22 . 2 = 23 x = 2(x + 5) 𝟑−𝟏𝟎 = (𝟑𝟐 )−𝟏𝟎+𝟓
𝒂𝒓 𝟐𝟐
4. 𝒔 = ar – s = 22 – 1 x = 2x + 10 𝟑−𝟏𝟎 = 𝟑−𝟐𝟎+𝟏𝟎
𝒂 𝟐
5. (ar )s = ar . s (22 )3 = 26 x – 2x = 10 𝟑−𝟏𝟎 = 𝟑−𝟏𝟎
6. (ab)r = arbr (3x)2 = 32 x2 = 9x2 -1(-x = 10) -1
𝒂 𝒂𝒓 𝟐 𝟐𝟐 𝟒 x = -10
7. ( )𝒓 = ( )𝟐 = =
𝒃 𝒃𝒓 𝟑 𝟑𝟐 𝟗
EXERCISES:
EXAMPLES:
Example 1. 𝟓𝟑𝒙 = 𝟓𝟕𝒙−𝟐 checking: Solve the following exponential equations.
𝟐
𝟏 𝟏 1. 𝟒𝒕 = 𝟒𝟔−𝒕
3x = 7x – 2 𝟓𝟑(𝟐) = 𝟓𝟕(𝟐)−𝟐
𝟑 𝟕 2. 𝟑𝟐𝒙−𝟏 = 𝟐𝟕
2 = 7x – 3x 𝟓𝟐 = 𝟓𝟐−𝟐 3. 𝟒𝒙+𝟏 =
𝟏
𝟑 𝟕−𝟒 𝟔𝟒
2 = 4x 𝟓𝟐 = 𝟓 𝟐
4. 𝟐𝟑𝒙+𝟓 = 𝟔𝟒𝒙−𝟕
𝟑 𝟑
𝟐
=
𝟒𝒙
𝟓𝟐 = 𝟓 𝟐 5. 𝟏𝟐𝟓𝒙−𝟏 = 𝟐𝟓𝒙+𝟑
𝟒 𝟒
𝟏
x=
𝟐
LESSON 11: EXPONENTIAL INEQUALITIES
Exponential inequalities are inequalities in the form 𝒂𝒇(𝒙) < 𝒃𝒈(𝒙) which
have variables in the exponent(s).

Examples:
Example 1.
𝟐𝟑x+𝟕 < 𝟐𝟐x−𝟏 checking:
3x + 7 < 2x – 1 𝟐𝟑(−7)+𝟕 < 𝟐𝟐(−7)−𝟏
3x - 2 x < -1 -7 𝟐−𝟐𝟏+𝟕 < 𝟐−𝟏𝟒−𝟏
x<-8 𝟐−𝟒 < 𝟐−𝟏𝟓
Example 2.
𝟒𝟑𝒙+𝟐 < 𝟔𝟒
checking:
𝟏
𝟒𝟑𝒙+𝟐 < 𝟒𝟑 𝟒𝟑(𝟒)+𝟐 < 𝟒𝟑
𝟑
𝟒𝟒+𝟐 < 𝟒𝟑
𝟑+𝟖
𝟑𝒙 + 𝟐 < 𝟑 𝟒 𝟒 < 𝟒𝟑
3x < 3 – 2 𝟒𝟏𝟏/𝟒 < 𝟒𝟑
𝟏
x<
𝟑
Exercises:
1. (4/6)x ≥ 36/16
2. 5x > 25x+1
3. 3x > 81
4. 43x+2 < 64
5. (49/81)x+1 ≥ 9/7
Key to correction:
LESSON 1:
1. F 3.
2. F
3. F
4. R
5. F
6. R
7. R LESSON 3.
8. R 1. f (5) = 14
9. F
10. F 2. f (2) = 9

LESSON 2. 3. f(5) = 11
1. We see that the “boundary points” are 15 and 40, since these are the
weights where prices change. Since we have two boundary points, we’ll have 4. f(b) = 3b2 + 2b + 1
three equations in our piecewise function. We have to start at 0, since dogs
have to weigh over 0 pounds: 5. f(h + 1)= 4h + 5

6. Incorrect. These equations look similar but are not the same. The first
has a slope of 2 and a y-intercept of −7. The second function has a slope of
−2 and a y-intercept of 7. It slopes in the opposite direction. They do not
produce the same graph, so they are not the same function. The correct
answer is f(x) = 3x2 + 5 and y = 3x2 + 5.
2.
7. g (-10) = -33
.
8. g (-10) = -23

9. 𝒇(−𝟑) = 𝟒
10. 𝒇(−𝟏) = 𝟐√𝟔
LESSON 4.
1. (f + g)(x) = –2x + 6
2. (f – g)(x) = 8x – 2 LESSON 5:
3. (f × g)(x) = –15𝒙𝟐 + 2x + 8 1.
𝒇 𝟑𝒙+𝟐
4. ( ) (𝒙)=
𝒈 𝟒−𝟓𝒙
5.(f * h) (x)
(3x + 2) (2x + 1) = 6x2+7x+2
6. k(x) ● f(x)
𝒙
k(x) ● f(x) = ( ) (2x)
𝟐
𝟐𝒙𝟐
k(x) ● f(x) = = x2
𝟐 2. (k○h)(x) = 54x + 71
7. g(x) - h(x) 3. 5x2 + 2
g(x) - h(x) = (x-2) - 𝒙𝟐 4. x2 - 4x - 1
= −𝒙𝟐 + x -2 or 𝒙𝟐 − 𝒙 + 𝟐 5. 15x - 38
8. h(x) + k(x) 6. √2x + 2
𝒙
h(x) + k(x) = 𝒙𝟐 + 7. x + 1
𝟐
𝟐𝒙𝟐 +𝒙 8. 5x + 1
=
𝟐 9. 3x
h(x) + k(x) = 𝒙𝟐 + 𝒙 10. 2√x + 1 + 1
9. f(x) ÷ k(x)
𝟐𝒙
f(x) ÷ k(x) = 𝒙 Lesson 6:
𝟐 1. 2. 3.
𝟐
= (2x) ( )
𝒙
𝟒𝒙
=
𝒙
f(x) ÷ k(x) = 4
10. g(x) ● h(x)
= (x – 2) (𝒙𝟐 )
4. 5.

g(x) ● h(x) = 𝒙𝟑 − 𝒙𝟐
Lesson 7: LESSON 9:
1. {x | ≤ 𝟎 } (-∞,0] Find the inverse of the following functions.
𝒙–𝟕
2.{x | -1 < x ≤ 5) (-1, 5] 1. f -1(x) = 𝟐
3.{x | x > -2} (-2, ∞) −𝟓𝐱−𝟐
2. f -1(x) =
4.{x | -2 ≤ x ≤ 2} [-2, 2] 𝟑𝒙−𝟏
5.{x | x ≥ 6} [6, ∞) 𝟑
Lesson 8: 3. f-1(x) = √−𝒙 + 𝟐
1.
4.

5.

6.

7.

8.

2. 9.
𝑥+7
10. =y
12

## LESSON 10: LESSON 11:

1. 1. {x | x ≤ -2} (-∞, -2]
2. {x | x < -2} (-∞, -2)
3. 2. 3. {x | x > 4} (4, ∞)

## 4. {x | x < 1/3} (-∞, 1/3)

3. 5 {x | x ≥ -1} [-1, ∞)
4. 47/3
5. x= 5